1975
DOI: 10.3758/bf03212921
|View full text |Cite
|
Sign up to set email alerts
|

The associative learning of the deaf: The effects of word imagery and signability

Abstract: In two experiments, deaf and hearing subjects learned paired associate lists in which rated visual imagery and signability (a measure of the ease with which a word can be represented as a gestural sign) were orthogonally varied. Visual presentation of three alternating study-recall trials resulted in significant positive effects of imagery for both deaf and hearing subjects, whereas signability facilitated recall only for deaf subjects. Examination of the relation between item attributes and reported learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 14 publications
(15 reference statements)
2
15
0
1
Order By: Relevance
“…These results suggest that hearing impaired individuals remember printed English words by recoding them into sign. Conlin and Paivio (1975) reported similar findings in their study of highly signable words, low signable words, high imagery words, and low imagery words, as did Treiman and Hirsh-Pasek (1983) in a task involving sentences. Their subjects had more difficulty judging sentences containing formationally similar signs than control sentences that did not contain similar signs.…”
Section: Recoding Strategies Of Hearing Impaired Readerssupporting
confidence: 74%
“…These results suggest that hearing impaired individuals remember printed English words by recoding them into sign. Conlin and Paivio (1975) reported similar findings in their study of highly signable words, low signable words, high imagery words, and low imagery words, as did Treiman and Hirsh-Pasek (1983) in a task involving sentences. Their subjects had more difficulty judging sentences containing formationally similar signs than control sentences that did not contain similar signs.…”
Section: Recoding Strategies Of Hearing Impaired Readerssupporting
confidence: 74%
“…Studies by Conlin & Paivio (1975) and Bonvillian (1983) first suggested that deaf individuals use some kind of veridical visual imagery code in place of ''verbal'' coding, although more recent studies have shown no greater visual imagery ability or non-verbal imaginal coding among deaf than hearing persons (Marschark, 1993). In this light, a reasonable alternative is that deaf individuals might make use of sign languagebased memory codes, and a variety of studies have demonstrated that lists of signs made with similar handshapes tend to disrupt memory performance while the relative availability of a sign (i.e., whether or not there is a familiar sign for a concept) is strongly related to recall (e.g., Bellugi et al, 1974;Poizner et al, 1981;Wilson & Emmorey, 1997).…”
Section: Working Memorymentioning
confidence: 97%
“…On the other hand, DHH signing children have sign-based representations which may support development of word reading skills. Indeed, experimental evidence indicates that there is a signbased route to word reading for DHH signers (Barca, Pezzulo, Castrataro, Rinaldi, & Caselli, 2013;Conlin & Paivio, 1975;Kubus, Villwock, Morford, & Rathman, 2015;Morford, Kroll, Piñar, & Wilkinson, 2014;Morford, Wilkinson, Villwock, Piñar, & Kroll, 2011;Ormel, Hermans, Knoors, & Verhoeven, 2012;Pan, Shu, Wang, & Yan, 2015;Treiman & Hirsh-Pasek, 1983). This is quite remarkable given that sign language and written language do not correspond in sub-lexical structure.…”
Section: Sign Language Skills and Learning To Read Wordsmentioning
confidence: 93%